Religion, science and ‘religious education’ in Russia six regional projects - Arinin E.; Chelovenko T.; Dorzhigushaeva O.; Glagolev V.; Markova N.; Matushanskaia I.; Sibirtseva I.; Vorontsova E. (2019)
© 2019, Ecozone, OAIMDD. All rights reserved. The research is carried out in the framework of the project 'Philosophical Religious Studies as a 'Glocal' Project: Youth of Germany and Russia in Dialogue on Religion', which received grant support from the Russian Foundation for Basic Research (18-011-00935 A, 2018-2020). It focuses on the issues of formation of local identities, combining 'religion', 'science' and 'education', which are being formed in the regions after the collapse of the USSR (1991), and on the adoption of the standards of freedom of conscience in modern Russia (Constitution, 1993). We represent the regions in order of their historical integration as part of the modern Russian Federation: Vladimir (990), Moscow (1147), Kazan (1552), Oryol (1566), Arkhangelsk (1584) and Ulan-Ude (1666). These cities act as urban centres, where political, economic, educational and religious elites are concentrated, and support and reproduce the 'collective memory' of 'Pax Christiana', 'Pax Islamica', 'Pax Buddhica', 'Pax Khazarica', 'Pax Tatarica' and 'Pax Sovietica', in global, local and 'glocal' forms of their construction in the system of public school education (since 2012-the course 'Basics of religious cultures and secular ethics').